IMPROVING SECONDARY STUDENTS' CAREER UNDERSTANDING THROUGH SOCRATIC DIALOGUE IN GROUP GUIDANCE - Habsy, Bakhrudin All; Anggraini, Faradita Ayu; Zulfah, Sayyidah Zakiyah (PT Altin Riset Publishing, 2025)
This research aims to assist students in formulating a mature career plan by understanding their interests and talents. Many students still do not know the career path they will take in the future due to a lack of understanding of their potential. Therefore, this study was conducted to provide intervention through group guidance with Socratic discussion techniques. This technique was chosen because it involves active dialogue between participants in groups to discuss career planning in depth. It is hoped that through an open and reflective dialogue process, students can broaden their horizons and change their views on careers based on the results of mutual exchange of ideas and knowledge. This study uses a quantitative descriptive method with a pretest and posttest approach to measure the effectiveness of the intervention carried out. The research sample consisted of 10 students out of a total of 30 students who were the subjects of the study. Each participant attended a group mentoring session facilitated by Socratic discussion techniques, and their understanding of career planning was evaluated before and after the intervention. The results of the study show that Socrates' discussion technique is effective in improving students' understanding of career planning. Participants become more open in thinking, more aware of their potential and interests, and have a clearer picture of the career path they want to take. This technique encourages participants to think critically and reflectively, thus helping them make more informed decisions in planning their future careers.